Examining the Role of Teachers in the Provision of Guidance and Counselling at Secondary School Level - Tahir Mehmood, Rahmat Ullah Bhatti, (JCTE, 2023)
Scientific and technological advancements have affected all walks of life and have brought about significant changes in them. Keeping in view the ever-changing nature of society, educational demands and needs, employment and religious exploitation, school students are under a lot of stress. The situation demands that they should be helped to cope with this stress. Educational guidance and counselling have played a vital role for students in this regard. The present study was planned to investigate the role of educators in providing guidance and counseling to students of secondary level. A descriptive survey design was used for this purpose. The participants were included through stratified sampling technique. These comprise principals, teachers and students of secondary schools in the Islamabad Capital Territory. Three separate questionnaires were designed for the participants. These included questionnaires for: the principals of secondary schools, students and teachers. The findings revealed that the teachers lacked the skills and knowledge required for providing guidance and counseling to the students. The current teacher education programs don’t equip teachers with the skills to provide guidance and counselling to students. In addition, the teachers are not ready to play the role of guidance counsellors. The analysis revealed that there did not exist any arrangement for providing guidance and counselling to the students.